PROGRAM MANAJEMEN STRES UNTUK PENDIDIK: SEBUAH PENDEKATAN MSDM - Mutaqin, Muhamad Zaenal (Expectation: Journal of Islamic Education Management, 2025)
One of the major problems faced by teachers around the world is occupational stress, which can negatively affect their health and performance. The purpose of this study is to find out how effective a stress management program based on Human Resource Management (HRM) is for educators. To gain a more in-depth understanding of educators' experiences during the program, a qualitative research approach was used. Data was collected through interviews with teachers and research of books and journals. The results showed that the program was effective in reducing educators' stress and improving their emotional well-being.